2015
DOI: 10.1186/s40168-015-0113-6
|View full text |Cite
|
Sign up to set email alerts
|

The functionality of the gastrointestinal microbiome in non-human animals

Abstract: Due to the significance of the microbiome on human health, much of the current data available regarding microbiome functionality is centered on human medicine. For agriculturally important taxa, the functionality of gastrointestinal bacteria has been studied with the primary goals of improving animal health and production performance. With respect to cattle, the digestive functions of bacteria in cattle are unarguably critical to digestion and positively impact production performance. Conversely, some research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
115
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(125 citation statements)
references
References 93 publications
2
115
0
1
Order By: Relevance
“…). These microorganisms in the gastrointestinal tract could process indigestible carbohydrates and provide nutrients and vitamins to their host (Aron‐Wisnewsky and Clément, ; Hanning and Diaz‐Sanchez, ). However, the well‐known health beneficial bacteria Lactobacillus and Bifidobacterium were not enhanced after YC treatments, different from the studies on the effects of prebiotic XOS dietary in chinken reported by Pourabedin et al .…”
Section: Discussionmentioning
confidence: 99%
“…). These microorganisms in the gastrointestinal tract could process indigestible carbohydrates and provide nutrients and vitamins to their host (Aron‐Wisnewsky and Clément, ; Hanning and Diaz‐Sanchez, ). However, the well‐known health beneficial bacteria Lactobacillus and Bifidobacterium were not enhanced after YC treatments, different from the studies on the effects of prebiotic XOS dietary in chinken reported by Pourabedin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Macro‐organisms harbour complex microbial communities living inside and on their body (Margulis, ; Theis et al, ). These microbial communities, known as the microbiomes, can determine pivotal phenotypic traits of their hosts, driving a variety of ecological and evolutionary processes including major nutritive, reproductive and immune functions (Gould et al, ; Groussin et al, ; Hanning & Diaz‐Sanchez, ; Ley et al, ; Turner, James, & Poole, ). As hosts vary in the microbiomes they harbour, an associated functionally important phenotypic variation exists within host populations (Falony et al, ; Ferrari & Vavre, ; Jaenike, ; Oliver, Russell, Moran, & Hunter, ; Scarborough, Ferrari, & Godfray, ).…”
Section: Introductionmentioning
confidence: 99%
“…The ecological community of bacteria that composes vertebrate gut microbiomes performs a set of metabolic functions (Coyte, Schluter, & Foster, ; Douglas & Werren, ), some of which benefit their host (Foster, Schluter, Coyte, & Rakoff‐Nahoum, ; Hanning & Diaz‐Sanchez, ). Since gut microbiomes aid in digestion (Rowland et al, ) and pathogen resistance (Stough et al, ), they are an essential mediators of their host's interaction with its broader biotic community.…”
Section: Introductionmentioning
confidence: 99%